If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-9-7d=-8d+1
We move all terms to the left:
-9-7d-(-8d+1)=0
We get rid of parentheses
-7d+8d-1-9=0
We add all the numbers together, and all the variables
d-10=0
We move all terms containing d to the left, all other terms to the right
d=10
| (x+3)2+(x-1)2=x+1+x+3+x+5 | | 5+8b=5(1-8b) | | 2=z-91/3 | | X+(x-15)+(x+21)=180 | | -2(x-5)=-3(x+2) | | 49x^2-64x=0. | | 60=5(12x+2) | | 3w-(-20)=74 | | 5/6t−2=3 | | 56t−2=3 | | 30+6p=4(1-5p) | | 16=31-5g | | 2x-11-4=-3 | | 4(3x-6)-4=-3x-6 | | -2+8k=-66 | | j/5-45=-35 | | 7=n/3-(-3) | | -28=13q | | 6(p-99)=-54 | | -1+10h=59 | | -2(x=-3(x+2) | | 10k+35=-55-5k | | z-33/9=5 | | P-5-13p=120-11 | | 15-2x-2=10x+3x×2 | | 6(1+6x)-2=2(6x+2) | | 6=3(g-7) | | -17=-2+3x | | -31-4=-5-5(1+5x | | 8x-11-2x=-6+10+9x | | 2/7(7u=14)-8=18 | | 21-2s=19 |